Methods for the Determination of Stable Isotope Ratios of Multiple Nitrogen Species in Rainwater Using Distillation and Evaporation - Jeong, Young-Jae; Seo, Bo-Seong; Baek, Nuri; Kwak, Jin-Hyeob; Lee, Sang-Mo; Park, Hyun-Jin; Choi, Woo-Jung (Frontiers in Environmental Science, 2022)
Nitrogen (N) isotope ratios (δ15N) of multiple N species including ammonium (NH4+), nitrate (NO3−), dissolved organic N (DON), and total dissolved N (TDN) can serve as indicators of the sources of wet N deposition. However, methods for sequential analysis of these multiple N species are not well developed. In this study, methods for the determination of δ15N of these multiple N species were proposed through a traditional distillation method for NH4+ and NO3−, direct evaporation for TDN, and an isotope mass balance equation for δ15N-DON. A series of experiments were conducted 1) to find evaporation conditions including pH (<3.5 vs. 5.4) and evaporation methods (oven drying at 60 and 100°C, infra-red chamber, and freeze-drying), 2) to investigate precision and accuracy of distillation for δ15N of NH4+ and NO3−, and 3) to determine δ15N-TDN by direct evaporation and δ15N-DON with mass balance equation. (NH4)2SO4 (‒4.0 ± 0.03‰), KNO3 (‒4.2 ± 0.03‰), and CO(NH2)2 (‒5.4 ± 0.04‰) were used as reference materials for NH4+, NO3−, and DON, respectively. In this study, for the analysis of δ15N of NH4+ and NO3−, the conventional distillation method was tested in an effort to save cost for laboratories equipped with the distillation system. Evaporation using oven at 60°C (but not 100°C), infra-red chamber, or freeze-drier after acidification to < pH 3.5 prevented 14NH3 loss. Analysis of the δ15N-NO3− (‒4.4 ± 0.1‰ to ‒3.9 ± 0.5‰) was reliable for a wide range of N content (0.1–0.5 mg), but analytical errors for δ15N-NH4+ were as high as 2.1‰ when N content was small (e.g., 0.1–0.3 mg N) due to background contamination and potential interference by co-existing DON. Direct evaporation of solution containing NH4+, NO3−, and DON to dryness produced reliable δ15N-TDN with accuracy <0.15‰ and precision <0.21‰. However, the analytical errors of δ15N-DON were highly dependent on the content of co-existing NH4+ as well as DON content. Therefore, the proposed protocol can be applied for rainwater containing a high NH4+ concentration (>2.0 mg N L−1 assuming that 200 ml of sample is used for distillation).